Onset dynamics of air-water menisci on rock fracture surfaces. (December 2020) - Horodecky, B.B.; Perfect, E.; Bilheux, H.Z.; Brabazon, J.W.; Gates, C.H.
Highlights: Vertical capillary rise of air-water menisci was measured on rock fracture faces. Meniscus onset and movement were imaged using dynamic neutron radiography. Apparent contact angles were calculated from the menisci heights at equilibrium. A linear relationship existed between these values and intrinsic contact angles. ABSTRACT: Information on menisci dynamics and equilibrium contact angles, θ e, is needed for modeling multiphase flow of fluids in geologic formations. The wettability of fracture faces is relevant to applications such as waterflooding in enhanced oil recovery and evaluation of caprock integrity for geologic carbon sequestration. We investigated the vertical capillary rise of air-water menisci on exposed fracture faces for a sandstone, a shale, and three granites. The experimental design approximated that employed in the Wilhelmy plate method. Replicate fracture faces were prepared by fracturing cylindrical rock cores using the Brazilian method and splitting the fractured cores apart along their fracture planes. Meniscus onset was imaged from a cross-sectional perspective using dynamic neutron radiography, and quantified with change point analysis. An existing model for meniscus onset fitted the experimental data very well (median R 2  = 0.96). Capillary rise was typified by t 2 3 scaling (where t is time), followed by a constant equilibrium height, ze . The average time taken for the menisci to reach ze was 0.39 s, with no differences between rock types. The menisci achieved a greater vertical extent on the fracture faces of the sedimentary rocks as compared to those of the granites. Apparent θ e values were calculated from the best fit estimates of ze using the Wilhelmy plate equation for a smooth and planar vertical surface. Despite the fractal roughness of some of the fracture faces, there was a significant linear relationship (R 2  = 0.80) between the apparent θ e values and intrinsic θ e values measured on polished surfaces of the same rocks using the sessile drop method. The regression equation indicated the apparent θ e values were consistently greater than the intrinsic values. This overestimation may be due to averaging of pixels at the air-water-solid interface, a required step in the image analysis. Further exploration of the range of applicability and measurement accuracy of this proposed new technique would be valuable.